Utilizing Instagram as a Social Commerce Marketing Strategy to Increase MSME Revenue - Indira Alifya; Aswat, Ibnu; Damayanti, Fera (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
At the moment, digital marketing is growing more rapidly than ever before, but through digital marketing a strategy is definitely needed so that revenue increases. However, previous research found that business people / entrepreneurs do not make the most of social media in their marketing strategies and do not realize the capabilities of existing social media. This research uses a qualitative approach with descriptive methods, aiming to gain insight related to the utilization of Instagram as a social commerce marketing strategy in increasing MSME revenues in the Lili Collection 31 case study. The data collection methods used are three, namely; observation, in-depth interviews and documentation studies. This research uses SWOT analysis to identify various factors both internal and external. The results of this study concluded that Lili Collection 31 has not been optimal and there is a need for improvement both in terms of understanding Instagram insights and marketing in attracting consumer interest.